DESIGN, FORMULATION, AND CHARACTERIZATION OF LIPOSOMAL-ENCAPSULATED GEL FOR TRANSDERMAL DELIVERY OF FLUCONAZOLE - S, Princely; Md, Dhanaraju (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objectives: The present objective for the study was to prepare proliposomal gel bearing an antifungal agent, fluconazole (FLZ) intended for topical application. Methods: Various proliposome formulations were prepared using thin-film hydration technique by varying the lipid phase composition (phosphatidylcholine/cholesterol). Proliposome formulations were characterized for vesicle size, vesicle size distribution, vesicle morphology, drug content, entrapment efficiency, percentage yield value, storage stability analysis, Fourier-transform infrared spectroscopy (FTIR), differential scanning calorimetry (DSC), in vitro diffusion study, release kinetic studies, and antifungal activity. Topical proliposomal gels were prepared by incorporation of lyophilized proliposome into a structured vehicle carbopol 934 (2.5%). Results: A spherical shape of reconstituted FLZ liposome with an average vesicle about 5–8 μm was observed in photomicrographs. The percentage entrapment of drug was increased with increase in phospholipid composition in the range of 55.13–69.61%. The FTIR and DSC studies showed no possible drug-excipient interaction. Proliposomal gel showed the prolonged release of FLZ than the lyophilized liposomes. The release kinetic values of regression coefficients confirmed the diffusion-dependent release of the drug. Stability studies indicated that product is stable and should be stored at low temperature. Conclusion: The proposed FLZ proliposomal gel showed sustained release with enhanced antifungal activity implicating its potential in effective transdermal delivery for the topical pharmacotherapy.